RECK in Neural Precursor Cells Plays a Critical Role in Mouse Forebrain Angiogenesis - Li, Huiping; Miki, Takao; Almeida, Glícia Maria de; Hanashima, Carina; Matsuzaki, Tomoko; Kuo, Calvin J.; Watanabe, Naoki; Noda, Makoto (iScience, 2019)
RECK in neural precursor cells (NPCs) was previously found to support Notch-dependent neurogenesis in mice. On the other hand, recent studies implicate RECK in endothelial cells (ECs) in WNT7-triggered canonical WNT signaling essential for brain angiogenesis. Here we report that RECK in NPCs is also critical for brain angiogenesis. When Reck is inactivated in Foxg1-positive NPCs, mice die shortly after birth with hemorrhage in the forebrain, with angiogenic sprouts stalling at the periphery and forming abnormal aggregates reminiscent of those in EC-selective Reck knockout mice and Wnt7a/b-deficient mice. The hemorrhage can be pharmacologically suppressed by lithium chloride. An effect of RECK in WNT7-producing cells to enhance canonical WNT-signaling in reporter cells is detectable in mixed culture but not with conditioned medium. Our findings suggest that NPC-expressed RECK has a non-cell-autonomous function to promote forebrain angiogenesis through contact-dependent enhancement of WNT signaling in ECs, implying possible involvement of RECK in neurovascular coupling. [Display omitted] •Mice lacking RECK in Foxg1-positive neural precursor cells die shortly after birth•These mice show vascular defects similar to those in mice lacking endothelial RECK•The vascular phenotype can be suppressed by LiCl, an activator of WNT signaling•RECK in WNT7-producing cell enhances contact-dependent WNT signaling in adjacent cells Vascular Remodeling; Neuroscience; Molecular Neuroscience; Developmental Neuroscience